Medical-psychological aspects of professional deformation of personality development among emergency medical staff - O. S. Lalymenko; І. V. Zavhorodnii; V. A. Kapustnyk; I. Boeckelmann; V. F. Zabashta; M. O. Stytsenko (Zaporožskij Medicinskij Žurnal)
The aim of the work. To study the specifics of professional burnout formation considering the relationship between its levels and typological personality traits of emergency medical staff.